A Small but Significantly Greater Incidence of Inflammatory Heart Disease Identified After Vaccination for Severe Acute Respiratory Syndrome Coronavirus 2. (30th December 2021) - Knowlton, Kirk U; Knight, Stacey; Muhlestein, Joseph B; Le, Viet T; Horne, Benjamin D; May, Heidi T; Stenehjem, Edward A; Anderson, Jeffrey L
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines are being administered on an unprecedented scale. Assessing the risks of side effects is needed to aid clinicians in early detection and treatment. This study examined the risk of inflammatory heart disease, including pericarditis and myocarditis, after SARS-CoV-2 vaccination. Methods: Intermountain Healthcare patients with inflammatory heart disease from December 15, 2020 to June 15, 2021, and with or without preceding SARS-CoV-2 vaccinations, were studied. Relative rates of inflammatory heart disease were examined for vaccinated patients compared to unvaccinated patients. Results: Of 67 patients identified with inflammatory heart disease, 21 (31.3%) had a SARS-Cov-2 vaccination within the previous 60 days. Overall, 914 611 Intermountain Healthcare patients received a SARS-CoV-2 vaccine, resulting in an inflammatory heart disease rate of 2.30 per 100 000 vaccinated patients. The relative risk of inflammatory heart disease for the vaccinated patients compared to the unvaccinated patients was 2.05 times higher rate within the 30-day window ( P = .01) and had a trend toward increase in the 60-day window (relative rate = 1.63; P = .07). All vaccinated patients with inflammatory heart disease were treated successfully with 1 death related to a pre-existing condition. Conclusions: Although rare, the rate of inflammatory heart disease was greater in a SARS-CoV-2-vaccinated population than the unvaccinated population. This risk is eclipsed by the risk of contracting coronavirus disease 2019 and its associated, commonly severe outcomes. Nevertheless, clinicians and patients should be informed of this risk to facilitate earlier recognition and treatment. Abstract : Inflammatory heart disease (pericarditis and/or myocarditis) is a rare post-SARS-CoV-2 vaccination event with a rate of 2.30 per 100 000 patients. The per-day rate for a 30-day postvaccine window is 2.05 times higher than for unvaccinated individuals.